Current Advances in Pharmaceutical Analysis and Method Development using High Performance Liquid Chromatography: Review Article (Journal of Pharma Insights and Research, 2025)
High Performance Liquid Chromatography (HPLC) is a versatile analytical technique in pharmaceutical analysis, offering superior resolution, sensitivity, and versatility. The technological evolution of HPLC instrumentation, coupled with sophisticated detection methods, has enabled precise quantification and qualification of pharmaceutical compounds at trace levels. The fundamental principles of HPLC encompass various separation modes, including reverse phase, normal phase, size exclusion, ion exchange, and bioaffinity chromatography, each serving specific analytical requirements. Modern HPLC method development incorporates systematic approaches in mobile phase selection, stationary phase optimization, and parameter adjustment to achieve optimal separation. The usage of Quality by Design (QbD) principles in method development has enhanced robustness and reliability in pharmaceutical analysis. Method validation parameters, including accuracy, precision, specificity, linearity, range, and system suitability, ensure the reliability of analytical results. HPLC applications extend across pharmaceutical quality control, stability studies, impurity profiling, and bioanalysis. Recent developments in HPLC technology, particularly in column chemistry and detection systems, have expanded its capabilities in complex pharmaceutical matrices analysis. The combination of HPLC with mass spectrometry has further increased its analytical scope, enabling structural elucidation and trace-level impurity profiling of pharmaceutical compounds